Recycling of Ceramic Bracket Using Burning Technique ( An in vitro study) - Omar H AL-Lwezy; Anas M AL-Mukhtar; Sarmad S. Salih (University of Mosul, College of Dentistry, 2010)
Aims: To study burning technique is tested for recycling of orthodontic ceramic bracket, then both re-cycled bracket and control (as received) bracket are tested for shear bond strength.Materials and Me-thods:The study samples are divided into two groups, control and test group. The brackets in the test group bonded, de-bonded and then recycled using burning technique, then both control and test group brackets are bonded to the buccal surface of premolar teeth and tested for shear bond strength. Re-sults:The result showed a complete removal of the composite resin from recycled bracket base, but a dramatic decrease in shear bond strength in recycled brackets compared with that of the new one Con-clusions:Ceramic bracket could not be efficiently used after recycling with burning technique since it will have a very low retention property.